Successful remote treatment of a client with Hikikomori using internet-delivered cognitive therapy for social anxiety disorder: a case report - Sakai, Motohiro; Yoshinaga, Naoki; Thew, Graham R.; Clark, David M. (Frontiers in Psychiatry, 2024)
Hikikomori (prolonged social withdrawal) has been discussed as a hidden worldwide epidemic and a significant social and healthcare issue. Social anxiety disorder is the most common psychiatric disorder preceding the onset of Hikikomori. Although studies exist suggesting the effectiveness of family-support interventions, little is known about psychotherapeutic approaches for Hikikomori individuals. Here, we present a case of Hikikomori wherein an internet-delivered cognitive therapy for social anxiety disorder (iCT-SAD) worked effectively in improving the client's social anxiety symptoms and social interaction behaviors. This case study demonstrates the principle that evidencebased psychological interventions focusing on social anxiety can be effective for clients with Hikikomori. Furthermore, the online mode of treatment delivery, along with a variety of relevant modules, may facilitate clients' engagement with treatment at home. The findings suggest that iCT-SAD might be a promising option for Hikikomori clients who have social anxiety problems, within the recommended stepped-intervention approach.